Legal and substantive standards in competition law enforcement: Relationships and jurisdictional variations - Katsoulacos Yannis (Anali Pravnog Fakulteta u Beogradu)
This article reviews recent literature on legal standards and substantive standards in competition law enforcement, with particular emphasis on the relationship between these two fundamental concepts, specifically on how the adoption of a specific substantive standard may affect the legal standards utilized by the courts and by competition authorities. We also examine the substantive and legal standards adopted in different jurisdictions, focusing on the EU (specifically, the EC) and the US, and discuss why legal standards are different in different countries.